Pelatihan Penggunaan Aplikasi Mendeley Dalam Penyusunan Tugas Akhir Bagi Mahasiswa Farmasi Universitas Megarezky - Andi Meinar Dwi Rantisari; Vivit Rosmayanti; Sriwahyuni Sriwahyuni; Muliaty Ibrahim; Sukmawati Sukmawati; Adriandy Saleh (Journal of Social Responsibility Projects by Higher Education Forum, 2023)
Writing scientific papers is one of the obligations of students as a condition for completing studies. However, in their preparation, students are often trapped in unintentional acts of plagiarism, namely copying and pasting a written work without putting in the source. Therefore, the existence of a software that functions as a "citation & reference manager" is a necessity. The Mendeley application helps students in inserting, writing, and formatting citations. This Community Service activity was held on Tuesday, June 7 2022 and was presented in the form of a workshop involving 40 final year Bachelor of Pharmacy students. The method of implementing the activity is divided into 3 systematic stages, namely education, device installation, and practice using Mendeley. The survey method was used to evaluate the results of the activity by distributing questionnaires to all participants before and after attending the training. The results of this activity were that after attending the training, all participants can use the Mendeley application well, starting from software installation on their respective devices, creating accounts, synchronizing the Mendeley application on MS Word, online library searches, and making bibliography automatically. with a customized citation style. The conclusion based on the survey results showed that there was a significant increase in the understanding and ability of Megarezky University Pharmacy students after attending the training. This shows that this activity has a positive impact in helping students manage citations and references in preparing their final project to avoid plagiarism.